Factors associated with oral biofilm in ICU patients with infectious diseases - Lecidamia Cristina Leite DAMASCENA; Larycia Vicente RODRIGUES; Raphael Cavalcante COSTA; Johnys Berton Medeiros DA NÓBREGA; Eugênia Lívia de Andrade DANTAS; Ana Maria Gondim VALENÇA (Universidade Estadual Paulista, 2017)
Abstract Introduction Hospitalization may cause a decline in oral health and affect the entire body. The intensive care unit (ICU) may be a favorable environment for oral biofilm to accumulate in critically ill patients. Objective To identify factors associated with oral biofilm in ICU patients in a hospital for infectious diseases. Method This was a retrospective, descriptive and inferential study with a quantitative approach. Data were collected from 178 medical records of patients from January 2012 to July 2015. Biofilm presence was assessed according to the Greene and Vermillion index. Potential influential factors were analyzed by logistic regression. Result Among ICU patients, 69.1% were men, 60.7% had acquired immune deficiency (AIDS), 66.3% were ward patients, 50.6% were intubated, and 50.0% were sedated. The oral elements of the patients were mostly normal. The following characteristics were significantly associated with oral biofilm: changes in the lips, gums, cheeks, and palates and bleeding. Patients from the ward had a lower risk of biofilm. Conclusion Increased oral biofilm accumulation was observed in patients with oral changes, and patient origin was associated with the presence of biofilm.